2014
DOI: 10.1002/jmri.24813
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of gleason scores with magnetic resonance diffusion tensor imaging in peripheral zone prostate cancer

Abstract: Quantitative DTI at 3.0T MRI shows a significant association with GS in the evaluation of tumor aggressiveness in peripheral zone PCa, which may be useful to ensure concordance of biopsy results and therefore make the appropriate decision in the management of patients with PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 40 publications
7
33
0
Order By: Relevance
“…These results are in agreement with previous literature where FA was reported higher for malignant tumors than for benign tumors . Similarly, low but measurable anisotropy values as the ones obtained in this study have been reported for cancers in other body organs, such as the prostate . Clinically, the use of DTI might complement standard DWI based on ADC solely.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with previous literature where FA was reported higher for malignant tumors than for benign tumors . Similarly, low but measurable anisotropy values as the ones obtained in this study have been reported for cancers in other body organs, such as the prostate . Clinically, the use of DTI might complement standard DWI based on ADC solely.…”
Section: Discussionsupporting
confidence: 93%
“…The aforementioned studies (23,24) demonstrated that the second factor served a leading role, thus reducing the FA value. However, the results of the present study were consistent with those from Li et al (22). We hypothesize that the first factor affecting the FA value had a greater impact; the freedom of movement of water molecules was restricted and although prostate inherent normal fiber bundles were destroyed, this led to more freedom of movement of water molecules, but very little impact, therefore, higher FA values were observed in patients with higher Gleason grades.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Li et al (22) reported that for PCa Gleason scores ≤3+3, 3+4, 4+3 and ≥4+4, ADC values were 1.11±0.16x10 (24) indicated that FA values and Gleason scores were negatively correlated, suggesting that an increase in Gleason scores would cause a gradual reduction in FA value. The main factors affecting the FA values are as follows: i) Following an increase in Gleason scores, the proliferation of mesenchymal structure of fibers and more closely arranged cells are observed, resulting in higher FA values; and ii) following an increase in Gleason score, the cell carcinoma is poorly differentiated, atypia increases and erosion of the fibrous tissue structure is enhanced, resulting in fiber breakage, as well as disorganized and restricted water diffusion, thus leading to decreased FA values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] However, any correlation between perfusion parameters and Gleason score could not be demonstrated, which is usually present between Gleason score, and MRI perfusion findings. [12,13] The aim of our study was to investigate the relationship between CTP parameters and histopathological features of PCa tissue using a comprehensive, sector-wise approach.…”
Section: Introductionmentioning
confidence: 99%